Perancangan Alat Ukur Portable Datalogger Pembangkit Listrik Tenaga Surya - A Noor, Nirwan; Sultan, Ahmad Rizal; Thaha, Sarma; Riyadi, Kazman; Lukman, Musfirah Putri (Jurnal Teknologi Elekterika, 2023)
Information about the output power of solar panels and the intensity of solar radiation is needed in the PLTS system to determine the characteristics of the potential power generated by the panels and estimate the amount of load attached. The purpose of this study was to design and manufacture a portable parameter measuring instrument and datalogger module on a microcontroller-based solar panel. Arduino Uno and ThingSpeak WebServer where with this measuring instrument solar panel parameters such as input parameters in the form of solar radiation, ambient (environment) temperature and output parameters in the form of voltage, current, latitude panel position will be measured, stored and displayed in graphical form in realtime. The system being built consists of three main parts: namely the sensor as input which will measure solar radiation data, temperature or temperature, current, voltage, latitude and longitude position of the Arduino Uno solar panel module which will acquire measurement data from sensors and the Labview application which will store and display data in realtime. The results of this study indicate that the measured current error is 1.68% and the lux error is 1.95%.